The Role of Prion Protein in Reelin/Dab1 Signaling: Implications for Neurodegeneration - Irene Giulia Rolle; Anna Burato; Merve Begüm Bacınoğlu; Fabio Moda; Giuseppe Legname (Viruses, 2025)
The cellular prion protein (PrPC) is studied in prion diseases, where its misfolded isoform (PrPSc) leads to neurodegeneration. PrPC has also been implicated in several physiological functions. The protein is abundant in the nervous system, and it is critical for cell signaling in cellular communication, where it acts as a scaffold for various signaling molecules. The Reelin signaling pathway, implicated both in Alzheimer’s and prion diseases, engages Dab1, an adaptor protein influencing APP processing and amyloid beta deposition. Here, we show, using Prnp knockout models (Prnp0/0), that PrPC modulates Reelin signaling, affecting Dab1 activation and downstream phosphorylation in both neuronal cultures and mouse brains. Notably, Prnp0/0 mice showed reduced responsiveness to Reelin, associated with altered Dab1 phosphorylation and Fyn kinase activity. Even though no direct interaction between PrPC and Reelin/ApoER2 was found, Prnp0/0 neurons showed lower NCAM levels, a well-established PrPC interactor. Prion infection further disrupted the Reelin signaling pathway, thus downregulating Dab1 and Reelin receptors and altering Reelin processing, like Alzheimer’s disease pathology. These findings emphasize PrPC indirect role in Dab1 signaling via the NCAM and Fyn pathways, which influence synaptic function and neurodegeneration in prion diseases.